Attitudes of Nursing and Midwifery School's Faculty toward Blended E-learning at Tehran University of Medical Sciences - M Zolfaghari (MSc.); MR Sarmadi (Ph.D); R Negarandeh (Ph.D); B Zandi (Ph.D); F Ahmadi (Ph.D) (Tehran University of Medical Sciences, 2009)
Background & Aim: Blended E-Learning is an educational method which has been used recently in higher education worldwide. So, it seems that it is crucial for the Iranian academic members to accept it as a new educational method. This study was conducted to investigate attitudes of the faculty of Nursing and Midwifery School at Tehran University of Medical Sciences toward blended E-learning. Methods & Materials: In this cross-sectional study, all faculty members of Tehran University of Medical Science (n=60) were recruited to the study. Data were gathered using validated and reliable self-designed questionnaires. The collected data were analyzed using SPSS software. Results: The response rate was 93.33% (n=56). Most of the respondents (85.7%) were female. The mean age was 44.88 (SD=5.6). The years of teaching ranged from 5-30 years (mean=16.75). The majority of the respondents (66%) had positive attitude toward blended e-learning; thirty four per cent had completely positive attitude and none of them had negative attitudes. About 41% reported that they were eager to provide their course syllabuses according to this approach and 87.5% said that they were willing to attend the blended e-learning education workshops. There were no significant relationships between demographic variables and the attitudes. There was a significant relationship between willing to attend the workshops and positive attitude toward blended e-learning (P=0.012). Conclusion: According to the positive attitude of the respondents toward blended e-learning, it is recommended that further studies take place in order to design and implement the approach in formal education in the school of Nursing and Midwifery of Tehran University of Medical Science.   Key words: attitude, blended e-learning, faculty, School of Nursing and Midwifery